2014
DOI: 10.1002/bem.21873
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency magnetic fields inhibit adipogenesis of human mesenchymal stem cells

Abstract: It was reported that obese (Ob/Ob) mice lose their weight and fat when treated with 0.5 T direct current electromagnetic fields. We also observed that 7.5 Hz, 0.4 T rotation of extremely low frequency magnetic fields (ELF-MF) has an inhibitory effect on obesity. Mesenchymal stem cells (MSCs) are multi-potent cells capable of differentiating to different MSC lineages, including adipose. We hypothesized that inhibitory effects of ELF-MF on obesity may be related to the differentiation of MSCs to adipocytes. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…The roles of the different Wnt ligands in bone homeostasis and bone diseases are not yet fully understood. There have been many clinical trials and experimental studies reporting that PEMFs modulate bone metabolism through the Wnt/β‐catenin pathway . However, few researchers have investigated the Wnt ligands involved in the process, except for Wnt1 and Wnt3a .…”
Section: Discussionmentioning
confidence: 99%
“…The roles of the different Wnt ligands in bone homeostasis and bone diseases are not yet fully understood. There have been many clinical trials and experimental studies reporting that PEMFs modulate bone metabolism through the Wnt/β‐catenin pathway . However, few researchers have investigated the Wnt ligands involved in the process, except for Wnt1 and Wnt3a .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Song et al found that the same EMF treatment could also inhibit adipogenic differentiation and promote osteogenic differentiation of BMSCs under the environment of dexamethasone (Song et al, 2014b). Similarly, Du et al documented that EMFs of 7.5 Hz, 0.4 T inhibited the adipogenic differentiation of MSCs via JNK-dependent Wnt signaling pathway (Du et al, 2014).…”
Section: The Effect Of Emfs On Cell Biologymentioning
confidence: 97%
“…New biologic treatments, gene therapy, and stem cell therapies are being developed, 197 which require the skills of pain medicine physicians to deliver the treatment agents into the disks. Extremely low-frequency magnetic fields have been found to have the ability to inhibit adipogenesis of human mesenchymal stem cells, 198 which may generate a new direction for stem cell therapies. We predict that regenerative medicine tools, including PRP and mesenchymal-derived stem cells, soon will replace many corticosteroid injections.…”
Section: Interventional Pain Management In Obese Patientsmentioning
confidence: 99%